Whitegrubs in potato and their control - S Chandel, R; Vashisth, Sumit; Verma, K S (Indian Horticulture, 2022)
Whitegrubs are highly polyphagous pests and damage almost all the field crops grown during rainy season. The potatoes grown during summer season as rainfed crop under long day conditions suffer maximum attack of whitegrubs. In India, 20 species of whitegrubs are known to damage potato. The tuber damage often exceeds 50% in endemic areas. B. coriacea is the most destructive species in the entire north-western Himalaya. H. longipennis and H. seticollis are predominant species in Uttrakhand. Melolontha indica is a localized species in certain pockets of north-western Himalaya, but its damage potential is manifolds higher as compared to B. coriacea and H. longipennis. For management of beetles, their mass collection and spraying of host trees with carbaryl (0.2%), quinalphos (0.05%), and chlorpyriphos (0.2%) has been found effective. Application of chlorpyriphos or quinalphos in first fortnight of June gives satisfactory control of whitegrubs. Metarhizium anisopliae, Beauvaria bassiana, Heterorhabiditis indica and H. bacteriophora also holds considerable potential to control these soil pests.